THE ARCHITECTURE OF TOMORROW: HOW LEGAL INNOVATION DRIVES AEROSPACE ENGINEERING AND GLOBAL TECHNOLOGICAL GOVERNANCE - Siddiqui, Hassan Rasheed (International Journal of Psychosocial Rehabilitation, 2025)
This study investigates the crosscutting relationship between technological innovation, regulations and impact on the proficiency of engineering, space and AI studies. And as technologies such as autonomous drones, satellite infrastructure, and AI-powered systems develop at breakneck speed, old-fashioned regulatory structures have a hard time keeping up, causing inefficiencies, delays, and stagnation. It is the contention of this paper that well-crafted and forward-looking regulatory environments are accelerants of technological development and not barriers to innovation. By closely examining historical and current regulatory deficiencies, the paper emphasizes the need for regulatory foresight to be built-in to technological development, as revealed in the case of the drone delivery systems and satellite logistics. Proactive regulation that anticipates trends and challenges resulting from technological progress can lead to regulation that adapts to innovation and helps achieve responsible and sustainable growth. The study concludes with recommendations for policy such as the formation of cross-disciplinary regulation bodies, real time adaptable law platforms, and universal space explorations treaties. Such proposals are intended to offer a legal foundation in which innovation is promoted and, but safety, data protection, ethical considerations, and international cooperation, are taken into account. The study highlights that properly designed regulation can provide the environment for safe, efficient and ethical innovation, in turn benefitting business, government and broader society. Ultimately, we posit that regulatory novelty is an empirical necessity for realizing the potential of new technology, as exemplified in the space domain and the case of AI, and for ensuring that technological advances serve humanity’s future.